OPTIMALISASI PENANGANAN WILDLIFE UNTUK MENINGKATKAN KESELAMATAN OPERASI PENERBANGAN DI BANDARA INTERNASIONAL RADIN INTEN II LAMPUNG - Ittabiana Nabawiyati; Ariyono Setiawan; Setyo Hariadi (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Safety first means top priority in the world of aviation, so that flights are carried out in safe and secure conditions according to the flight plan supported by flights that are free from disturbances or act against the law. In a month, Radin Inten II International Airport has experienced nine wildlife incidents, this indicating that flight safety at Radin Inten II International Airport Lampung needs to be optimized. The research method used is descriptive qualitative by referring to the SKEP/42/III/2010 regulation on "Instructions and Procedures for Civil Aviation Safety Regulations Section 139-03 Hazard Management of Liar Animals at Airports and Surroundings". Methods of data collection using the method of observation, literature study and interviews. The method used to test the data is to test the validity of the data including the credibility, transferability, dependability, and confirmability tests. The results of this study indicate that the quality of WHMP handling affect flight safety and security. Meanwhile, the results of data test show that the quality of WHMP handling at the airport was still not optimal, as evidenced by incidents and several factor that did not support WHMP optimization. The results of this study are expected to optimize WHMP of Radin Inten II International Airport, Lampung.